Pengaruh Komunikasi Organisasi Terhadap Kinerja Karyawan Richeese Factory Cabang Surabaya - Perkasa, M Ariananda; Wibowo, Judhi Hari; Norhabiba, Fitri (representamen, 2018)
This study aims to examine and analyze the effect of organizational communication on employee performance in Surabaya factory branch. Data collection was carried out through questionnaires and carried out on 90 employees at Richeese Factory located in Surabaya namely Richeese Factory Royal Plaza, Masqueion Square Richeese Factory, Richeese Factory Cito, Richeese Factory Spazio, Richeese Factory Plaza Surabaya and Richeese Factory Tunjungan Plaza 2. The sampling technique in this study was total sampling. Data analysis in this study uses SPSS version 24. This study uses hypothesis testing with ordinal regression method. Before being tested with this method the researcher conducted a descriptive analysis, validity test and reliability. Based on the parameter estimate table, organizational communication variables are 8,213 with sig. 0,04 (<0,05). If the significance level obtained is less than 0.05, then the variable regression coefficient is significant, and states that the independent variable is significant in influencing the dependent variable. The results of the analysis show that organizational communication has a significant positive effect on employee performance.Keywords: Organizational Communication, Organizational Communication Performance, Employee Performance, Leadership Style